ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI DI INDONESIA - Friska Cahya Yumanda (2023)
Indonesia requires foreign debt finance to fund its development, leading the country's foreign debt to grow every year. The purpose of this study is to examine the factors that influence Indonesian foreign debt using time series data from 1989 to 2021 and Autoregressive Distributed Lag (ARDL) approach. The results showed that in the short-term model, the fiscal deficit variable in the current year, lag 1st and lag 3rd had a significant positive effect on foreign debt, the foreign direct investment had no effect on external debt and net exports current period have a significant negative impact on foreign debt, while net exports lag 1st and 3rd have a significant negative effect on foreign debt. In the long-term model, all variables have no significant effect on foreign debt.